Cost-Effectiveness of the Quantification of Enzymatic Activity in Leukocytes in Comparison to Its Nonrealization for a Rare Disease in Latin America: The Case of Mucopolysaccharidosis Type II in Colombia (2016)
Background: Mucopolysaccharidosis (MPS) type II is produced by a deficiency of iduronate-2-sulfatase (I2S). The quantification of the enzyme activity in leukocytes is used as diagnostic confirmation of MPS. Objective: To determinate the cost-effectiveness of the measurement of I2S enzyme activity in leukocytes compared with not carrying out the enzyme activity measurement for diagnostic confirmation of MPS II from the perspective of the Colombian health system. Methods: A cost-effectiveness analysis was conducted on the basis of a decision tree model. The measure of effectiveness was the correct diagnosis of cases of MPS II. The costs of I2S enzymatic quantification in leukocytes, consultation with a geneticist and with other specialists, and costs of diagnostic procedures were included. The time horizon was less than 1 year. A probabilistic sensitivity analysis was performed using Monte-Carlo simulation with 10,000 iterations. Results: The incremental cost was -US $43,145 with an incremental effectiveness of 42 cases. The probabilistic sensitivity analysis confirms the results of basal data, in which the quantification of I2S enzyme activity was less costly and more effective than the alternative. Conclusions: The quantification of I2S enzymatic activity is a dominant technology for the diagnostic confirmation of MPS II, compared with not making the quantification, from the perspective of the Colombian health system. © 2016 International Society for Pharmacoeconomics and Outcomes Research (ISPOR).